Text linguistics: an overview and key issues (Eurasian Journal of Philology Science and Education, 2023)
The article is devoted to the development of text linguistics in modern linguistics. The article gives an overview of the research of scholars who have studied and are studying text linguistics, and analyses the current problems of text linguistics. In the last twenty years the interest to the mentioned direction of linguistics has been growing at a special pace in foreign and domestic science. An analytical review of the works of research scientists is made. This article discusses generalisation, comparison, monitoring, accounting, analysis and other methods have been used. In addition, several areas of text linguistics that are currently developing are reviewed. The object of the study of text linguistics was to compare and group the opinions of scholars concerning text. The paper analyses the reasons and necessity of studying text linguistics. It is shown that the study of topical problems is related to text theory. In addition, during the literature review, references from foreign and domestic research papers mentioned throughout the text were sorted and presented in a systematised way. The article deals with the theoretical aspect of text linguistics and touches upon the structural system of text. This article discusses the past, present and future of text linguistics.Key words: linguistics, text, text linguistics, speech, language, analysis.